Religious Civil Society Organizations Responses toward Democratic Decline: A Comparison between Nahdlatul Ulama and Muhammadiyah - Arifianto, Alexander R. (Faculty of Islam Nusantara, Nahdlatul Ulama University of Indonesia (Unusia) Jakarta., 2024)
This study seeks to explain the factors that lead religiously based civil society organizations to consistently cooperate with, or instead oppose, (semi-)authoritarian regimes. It also examines how the historical accumulation of religious competence can shape an organization’s political choices over time. The study employs a comparative case-study design, offering an in-depth historical analysis of the political responses of Indonesia’s two largest Islamic organizations, Nahdlatul Ulama (NU) and Muhammadiyah, within the context of democratic backsliding. The findings show that the divergent political strategies of NU and Muhammadiyah are shaped by two primary factors. First is the extent to which each organization’s ideology differs from that of emerging Islamist groups. Second is the degree to which the organizations’ follower bases shift toward these Islamist actors. With an ideological profile more clearly distinct from Islamism and a relatively large and loyal constituency, NU has tended to align with the government, including supporting restrictive measures against Islamist groups. Muhammadiyah, by contrast, has faced stronger competitive pressures due to certain ideological proximities with Islamism and a follower base more vulnerable to erosion. These conditions have encouraged Muhammadiyah to adopt a more critical stance toward democratic backsliding, while also defending Islamist groups subjected to state repression. This article contributes to scholarship on modern Islamic history, civil society, religion and politics, and democracy in Indonesia by demonstrating that intra-religious competence and historically shaped constituency dynamics constitute key variables for explaining patterns of collaboration and resistance among Islamic organizations in relation to the state.